Monocyte Chemoattractant Protein-1 (MCP-1/CCL2) Levels and Its Association with Renal Allograft Rejection. (3rd April 2017) - Raza, Ali; Firasat, Sadaf; Khaliq, Shagufta; Khan, Abdul Rafay; Mahmood, Shafaq; Aziz, Tahir; Mubarak, Muhammad; Naqvi, Syed Ali Anwar; Rizvi, Syed Adibul Hasan; Abid, Aiysha
ABSTRACT: Background : CCL2 is a chemoattractant for monocytes/macrophages, T cells, and natural killer cells. It is shown to be involved in the immunological responses against renal allograft. This study was conducted to access the role of urinary CCL2 expression in predicting the rejection episodes in renal transplant patients. Method : A total of 409 urine samples included in this study. The samples were consisted of (a) biopsy-proven graft rejection ( n = 165); (b) non-rejection ( n = 93); (c) non-biopsy stable-graft ( n = 42), and (d) healthy renal donors ( n = 109). The samples were quantified for the CCL2 using the MCP-1/CCL2 ELISA kit. The data were analyzed using the Statistical Package for Social Sciences (SPSS ® ) and MedCalc ® statistical software. Results : Results showed that the CCL2 levels were significantly increased in rejection group when compared with the non-rejection, stable-graft, and control, P < 0.05. The receiver operating curve's characteristics illustrated that the urinary CCL2 level is a good predictor for graft rejection, with an area under the curve of 0.81 ± 0.03 with optimum sensitivity and specificity of 87% and 62%, respectively, at a cut-off value of 198 pg/mL. Kaplan–Meier curve also showed better cumulative rejection-free graft survival time in group with less than 198 pg/mL of CCL2 as compared to those with expression levels of more than 198 pg/mL (30 weeks vs. 3 weeks; log-rank test, P < 0.001). Conclusion : In our study, noninvasive investigation of CCL2 levels in urine has showed potential to predict rejection episodes. It is suggested that the CCL2, with others markers, may help in early detection and monitoring of graft rejection episodes.